Potential of Malaysian cherry leaves (muntingia calabura) as an antioxidant agent / Noor Hidayah Pungot, Nurul Auni Zainal Abidin and Nur Syafiqah Atikah Nazaharuddin - Pungot, Noor Hidayah; Zainal Abidin, Nurul Auni; Nazaharuddin, Nur Syafiqah Atikah (Faculty of Applied Science, 2020)
Muntingia calabura has a high phytochemical content, especially the phenolic group that can act as antioxidant. In Malaysia country, this M. calabura also known as ‘kerukup siam’ or ‘Ceri Kampung’ and it belongs to Muntingiaceae family. This research was conducted to determine the potential of antioxidant activity application of cherry leaves (M. calabura) from various solvent extracts (methanol, ethyl acetate, and n-hexane). The phytochemical contents were screening by using the established standard procedure. Total phenolic content (TPC) was determined according to the Folin-Ciocalteau colorimetric method, while the antioxidant activity was carried out using 2,2-diphenyl-1-picryhydrazyl (DPPH) radical scavenging assay. Phytochemical screening on the leaves part methanolic extracts revealed that the presence of various biochemicals like flavonoids, phenols, steroids, triterpenes, tannins, reducing sugars, and saponins except the alkaloids. Among the three extracts, the methanol leaf extract gave the highest content of phenolics (8.20 mg GAE/g extract). Analyses of antioxidant activity with DPPH method showed that cherry leaf methanolic extracts produced high antioxidant activity with IC50 value of 167.70 g/mL. The present study confirms that the presence of various phytochemicals which shows good antioxidant activity of M. calabura leaves. Therefore, it has the potential as a therapeutic antioxidant agent and can be used in cosmeceutical and food products.